Visual loss due to optic nerve infarction and central retinal artery occlusion after spine surgery in the prone position: A case report. Issue 31 (August 2017) - Lee, Soo Hee; Chung, Inyoung; Choi, Dae Seob; Shin, Il-Woo; Kim, Sunmin; Kang, Sebin; Kim, Ji-Yoon; Chung, Young-Kyun; Sohn, Ju-Tae
Abstract: Rationale: Visual loss after spine surgery in the prone position is a serious complication. Several cases of central retinal artery occlusion with ophthalmoplegia after spine surgery have been reported in patients with ophthalmic arteries fed by the internal carotid artery (ICA) in a normal manner. Patient concerns: A 74-year-old man developed visual loss after undergoing a spinal decompression and fusion operation in the prone position that lasted approximately 5 hours. Diagnoses: We detected an extremely rare case of visual loss due to optic nerve infarction and central retinal artery occlusion through fundoscopic examination, fluorescein angiogram, brain magnetic resonance imaging, and magnetic resonance angiography. The patient's visual loss may have been caused by compromised retrograde collateral circulation of the ophthalmic artery from branches of the external carotid artery in the presence of proximal ICA occlusion after a spinal operation in the prone position. Interventions: To recover movement of the left extraocular muscles, the patient received intravenous injections of methylprednisolone for 3 days and then oral prednisolone for 6 days. Outcomes: Twenty days after the treatment, the motion of the left extraocular muscles was significantly improved. However, recovery from the left visual loss did not occur until 4 months after the operation. Lessons: In high-risk patients with retrograde collateral circulation of the ophthalmic artery from the external carotid artery due to proximal ICA occlusion, various measures, including the use of a head fixator to provide a position completely free of direct compression of the head and face, should be considered to decrease the risk of postoperative visual loss.